Tobacco use among students aged 13–15 years in Greece: the GYTS project - Kyrlesi, Athina (BioMed Central, 2007)
BACKGROUND: Data on the prevalence of tobacco use among teenagers in Greece are limited. We examined the prevalence of smoking among middle-school students in Greece using the Global Youth Tobacco Survey (GYTS). METHODS: The Global Youth Tobacco Survey was implemented in Greece during the academic year 2004 – 2005 by the University of Thessaly and the National School of Public Health. Data were collected using the GYTS self-administered anonymous questionnaire, which was distributed by specifically trained field workers to a nationally representative sample of middle-school students aged 13–15 years (through randomly selected schools and classes), randomly selected through a two-stage cluster sample design. Data processing and statistical analyses were performed at the Centers for Disease Control and Prevention (CDC). RESULTS: About one third of the students 32.1% (29.4 – 35.0) reported that they had tried tobacco in the past, while 16.2% (14.3 – 18.4) reported being current users of tobacco products. In addition, 1 in 4 of ever smokers reported that they began smoking before the age of 10 years old. Almost 1 in 5 never smokers reported being susceptible to initiate smoking in the next year and about 89.8% (88.3 – 91.1) of the respondents were exposed to environmental tobacco smoke in their homes and 94.1% (93.2 – 94.9) in public places. Finally, a strikingly high number of students 95% (89.5 – 97.7) reported that they were able to buy their own cigarettes without restrictions. CONCLUSION: The results of the GYTS show that the prevalence of smoking in middle-school children is alarmingly high in Greece. Smoking among young people constitutes a significant problem that is destined to worsen in the absence of any comprehensive efforts focused on strict anti-smoking legislation, policies and tobacco control interventions targeting children at a young age.